The Advancement of Catholicism in Britain as seen by the Nineteenth-Century Portuguese Press (1869-1890) - Terenas, Gabriela Gândara (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
.